2018
DOI: 10.3389/fnins.2018.00092
|View full text |Cite
|
Sign up to set email alerts
|

On the Viability of Diffusion MRI-Based Microstructural Biomarkers in Ischemic Stroke

Abstract: Recent tract-based analyses provided evidence for the exploitability of 3D-SHORE microstructural descriptors derived from diffusion MRI (dMRI) in revealing white matter (WM) plasticity. In this work, we focused on the main open issues left: (1) the comparative analysis with respect to classical tensor-derived indices, i.e., Fractional Anisotropy (FA) and Mean Diffusivity (MD); and (2) the ability to detect plasticity processes in gray matter (GM). Although signal modeling in GM is still largely unexplored, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…In particular, RTOP has also demonstrated to be a better indicator for cellularity and diffusion restrictions than the DTI-related mean diffusivity (MD) (Avram et al, 2016) and, together with MSD, a proper measure for the assessment of myelination (Alimi et al, 2018). These results were later confirmed by Boscolo Galazzo et al (2018), where the authors reinforced the hypothesis on RTOP to have greater specificity to reflect cellularity and restricted diffusion.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In particular, RTOP has also demonstrated to be a better indicator for cellularity and diffusion restrictions than the DTI-related mean diffusivity (MD) (Avram et al, 2016) and, together with MSD, a proper measure for the assessment of myelination (Alimi et al, 2018). These results were later confirmed by Boscolo Galazzo et al (2018), where the authors reinforced the hypothesis on RTOP to have greater specificity to reflect cellularity and restricted diffusion.…”
Section: Introductionmentioning
confidence: 61%
“…Although the use of these measures is not generalized among the clinical community, there is a growing interest on the exploration of their potential clinical applicability. To date, the relevance of scalar descriptors of the brain microstructure has been proved on both ex vivo (Daianu et al, 2015;Ozarslan et al, 2013;Fick et al, 2016a) and in vivo studies of healthy and diseased subjects (Brusini et al, 2015;Hosseinbor et al, 2012;Avram et al, 2016;Brusini et al, 2016;Boscolo Galazzo et al, 2018;Zucchelli et al, 2016). In particular, RTOP has also demonstrated to be a better indicator for cellularity and diffusion restrictions than the DTI-related mean diffusivity (MD) (Avram et al, 2016) and, together with MSD, a proper measure for the assessment of myelination (Alimi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Within the gray matter, the principally cellular microstructure typically has predominant isotropic diffusion characteristics that are best evaluated by apparent diffusion coefficient (ADC) maps . However, multiple studies have shown that FA values, markers of anisotropic diffusion, may also alter the microstructural anatomy if affected by a diffuse process . For example, in patients with a cortical stroke, the FA values may increase within the cortical gray matter, likely secondary to a combination of cytotoxic and vasogenic edema impacting the diffusion of water molecules within the extracellular space .…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of these measures is not generalized among the clinical community, there is a growing interest in the exploration of their potential clinical applicability. To date, the relevance of scalar descriptors of the brain micro-structure has been proved on both ex vivo [12,25,26] and in vivo studies of healthy and diseased subjects [22,23,[27][28][29][30]. In particular, RTOP has also demonstrated to be a better indicator for cellularity and diffusion restrictions than the DTI-related mean diffusivity (MD) [22] and, together with MSD, a proper measure for the assessment of myelination [31].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, RTOP has also demonstrated to be a better indicator for cellularity and diffusion restrictions than the DTI-related mean diffusivity (MD) [22] and, together with MSD, a proper measure for the assessment of myelination [31]. These results were later confirmed by [29], where the authors reinforced the hypothesis on RTOP to have greater sensitivity to reflect cellularity and restricted diffusion.…”
Section: Introductionmentioning
confidence: 99%